Source characteristics of the 2015 Mw6.5 Lefkada, Greece, strike-slip earthquake - Melgar, Diego; Athanassios Ganas; Geng, Jianghui; Liang, Cunren; Fielding, Eric J.; Ioannis Kassaras (Journal of Geophysical Research: Solid Earth, 2017)
Abstract We present a kinematic slip model from the inversion of 1 Hz GPS, strong motion, and interferometric synthetic aperture radar (InSAR) data for the 2015 Mw6.5 Lefkada, Greece, earthquake. We will show that most of the slip during this event is updip of the hypocenter (10.7 km depth) with substantial slip (>0.5 m) between 5 km depth and the surface. The peak slip is  1.6 m, and the inverted rake angles show predominantly strike-slip motion. Slip concentrates mostly to the south of the hypocenter, and the source time function indicates a total duration of  17 s with peak moment rate at  6 s. We will show that a 65° dipping geometry is the most plausible due to a lack of polarity reversals in the InSAR data and good agreement with Coulomb stress modeling, aftershock locations, and regional moment tensors. We also note that there was an  20 cm peak-to-peak tsunami observed at one tide gauge station 300 km away from the earthquake. We will discuss tsunami modeling results and study the possible source of the amplitude discrepancy between the modeled and the observed data at far-field tide gauges.
Keywords: source inversion; strike-slip continental fault